MOTIVATION OF CHILDREN'S HEALTH SCREENING VOLUNTEERS AT PUSKESMAS CIPTOMULYO AND MULYOREJO, MALANG CITY - Aloysia Ispriantari; Dian Pitaloka Priasmoro (Jurnal Kesehatan Mesencephalon, 2022)
In 2019, Children's Health Screening was held because there is volunteers from universities in Malang City. This volunteers motivation needs to be concerned because it is requires a lot of energy and time. The study was to determine the motivation of volunteers for School Children's Health Screening at Puskesmas Ciptomulyo and Mulyorejo. Respondents are volunteers for health screening at Puskesmas Ciptomulyo and Mulyorejo with total respondents are 34 respondents. Data was collected using “The Volunteer Functions Inventory” instrument. Data presented in descriptive and then used the unpaired t-test for analysis. The result is most of them (97.1%) of respondents had high motivation and the rest of them (2.9%) had moderate motivation. The factor of motivation that affect volunteers as following: understanding, career development, self-enrichment, personal value, self-protection and social factors. In addition, there is no difference in the motivation of volunteers based on the years of college education. Based on the results of this study, we suggest that academic institution prepare students to improve their clinical skills and motivate students to take part in volunteer activities in the community. Keywords: Motivation, Volunteers, School Children’s Health Screening